Evaluasi penerapan belanja modal berdasarkan Peraturan Pemerintah No. 12 Tahun 2019 di Pemerintah Kota Manado - Kambey, Novel Hiskya; Runtu, Treesje; Mawikere, Lidia M. (Riset Akuntansi dan Portofolio Investasi, 2024)
Capital expenditure is defined as budget expenditure for the acquisition of fixed assets and other assets that provide benefits for more than one accounting period. The types of capital expenditure are as follows: land expenditure, equipment and machinery expenditure, building and construction expenditure, road, irrigation and network expenditure, other fixed asset expenditure, and other asset expenditure. This research evaluates the implementation of capital expenditure in the Manado City Government based on Government Regulation no. 12 of 2019 concerning Regional Financial Management. It uses a qualitative descriptive method, collecting data through interviews and documentation. The evaluation results show that the implementation of capital expenditure in the Manado City Government is in accordance with Government Regulation No. 12 of 2019.